Validation and Application of a New Reversed Phase HPLC Method for In Vitro Dissolution Studies of Rabeprazole Sodium in Delayed-Release Tablets - Md. Saddam Nawaz (Journal of Analytical Methods in Chemistry)
The purpose of this study was to develop and validate a new reversed phase high performance liquid chromatographic (RP-HPLC) method to quantify in vitro dissolution assay of rabeprazole sodium in pharmaceutical tablet dosage form. Method development was performed on C 18, 100×4.6 mm ID, and 10 μm particle size column, and injection volume was 20 μL using a diode array detector (DAD) to monitor the detection at 280 nm. The mobile phase consisted of buffer: acetonitrile at a ratio of 60 : 40 (v/v), and the flow rate was maintained at 1.0 mL/min. The method was validated in terms of suitability, linearity, specificity, accuracy, precision, stability, and sensitivity. Linearity was observed over the range of concentration 0.05–12.0 μg/mL, and the correlation coefficient was found excellent >0.999. The method was specific with respect to rabeprazole sodium, and the peak purity was found 99.99%. The method was precise and had relative standard deviations (RSD) less than 2%. Accuracy was found in the range of 99.9 to 101.9%. The method was robust in different variable conditions and reproducible. This proposed fast, reliable, cost-effective method can be used as quality control tool for the estimation of rabeprazole sodium in routine dissolution test analysis.